Dimensions of execution quality: Recent evidence for US equity markets - BOEHMER, E (Journal of Financial Economics, 2005)
I analyze market-order execution quality using order-based data reported in accordance with Securities and Exchange Commission Rule 11Ac1-5. These data facilitate a comprehensive investigation of multiple dimensions of execution quality, including measures of costs and speed, for large samples of common stocks on Nasdaq and the NYSE. The evidence is consistent with competitive equity markets. Overall execution costs on Nasdaq exceed those on the NYSE, but orders execute faster. This relationship reverses for larger orders exceeding 1,999 shares. The apparent trade-off between costs and speed suggests that inferring execution quality from costs alone could be problematical. It also illustrates the need for models of trader behavior that can accommodate multiple dimensions of execution quality.